Quality of life of women with urinary incontinence in the postpartum period: an integrative literature review - Lopes, Filipa Daniela; Henriques, Carolina; Lopes, Maria da Saudade; Mendes, Isabel Margarida (Frontiers in Global Women's Health, 2025)
Urinary incontinence (UI) during pregnancy and after childbirth can negatively impact women's lifestyles, health, and well-being. It is a common problem that is often normalized by both healthcare professionals and women. This integrative review examines the influence of UI on women's quality of life (QoL) during the postpartum period and identifies the main affected domains. It will also contribute to the discussion of the results of a primary study. Fourteen studies were included in this review, mainly from Brazil and Spain, with most using quantitative methods. The findings indicate that UI negatively affects the QoL of women during the postpartum period, with mixed UI causing greater discomfort despite stress UI being more frequent. The main affected domains are general health perception, physical functioning, daily life activities, psychological/emotional/mental and social aspects, and sexuality. Effective interventions should promote women's self-care and enhance their awareness and recognition of the problem. These interventions should go beyond physical aspects to address emotional and psychological dimensions, such as low self-esteem and self-image, secrecy, embarrassment, and reluctance to seek help. Nurse midwives have specialized skills and can work within multidisciplinary teams to improve the QoL of women with UI at a time of increased vulnerability.